Palmatine potentiates cefquinome efficacy against multidrug-resistant Escherichia coli via sulfur/taurine metabolism and oxidative stress modulation - Zhang, Yining; Tong, Yinchao; Li, Pengcheng; Zhu, Leixin; Zhang, Hao; Xie, Honglin; Nasir, Saba; Li, Wei; Fang, Mingjin; Wang, Juan; Qing, Suzhu; Wang, Xinglong; et al. (Frontiers in Microbiology, 2025)
Palmatine, a natural isoquinoline alkaloid derived from Fibraureae Caulis, is widely used for its heat-clearing, detoxifying, antibacterial, and anti-inflammatory properties. The emergence of multidrug-resistant Escherichia coli poses a critical challenge to the efficacy of β-lactam antibiotics, particularly cephalosporins such as cefquinome. This study demonstrates that palmatine markedly enhances the antibacterial activity of cefquinome through multi-targeted mechanisms, revealing a new pharmacological potential for this compound. Antimicrobial and synergistic activities were assessed using the microbroth dilution method and checkerboard assay. Bacterial morphology was examined using scanning electron microscopy (SEM), while biofilm inhibition was assessed using confocal laser microscopy. Membrane damage and reactive oxygen species (ROS) levels were detected with fluorescent probe dyes. Transcriptome and RT-qPCR analyses were conducted to identify key mechanistic pathways, and the synergistic effect was further validated in a mouse Escherichia coli infection model. In vitro analyses of 20 tested isolates revealed broad synergistic effects (FICI ≤ 0.5), with cefquinome MICs reduced by 4- and 32-fold. Mechanistic studies revealed that palmatine disrupts membrane integrity, potentiates oxidative stress, and inhibits biofilm formation. Transcriptomic profiling implicated sulfur metabolism as a key pathway, showing that palmatine reversed cefquinome-induced downregulation of sulfur metabolism-related genes. Functional validation confirmed that disruption of taurine uptake in the sulfur metabolic pathway eliminated the synergistic effect. In murine infection models, the combination therapy increased survival by 30%, alleviated diarrhea, and significantly reduced bacterial loads in tissue. This study reveals the novel pharmacological properties of palmatine, identifies metabolic-level reversal regulation as a novel strategy to combat β-lactam resistance, and highlights palmatine as a multi-target adjuvant that enhances cefquinome efficacy against resistant Gram-negative infections.